Rancang Ulang Punch-Dies untuk Pembuatan Outlet Pipe I di PT. Ionuda Surabaya - Pandiatmi, Pandri (Jurnal Rekayasa Mesin, 2010)
In the preparation process of outlet pipe I type 316N, an imperfect shape occurs when it is combined with its part/ Base on the analysis conducted, spring back on forming process occurs so that it makes the size of diameter of outlet pipe improper after combined with its parts. There are several methods that can be used to eliminated springback, but for this case, a graphical approach is conducted to calculate the addition of punch-dies geometry as the compensation of springback. Punch-dies reconstruction for preparation process outlet pipe I by inserting material springback factor, dies radius (Rdo)=19.14mm and punch radius (Rpo) = 17.92 mm.Keywords : punch, dies, springback,, forming process